Supplement to Neurospora bibliographies: Chrysonilia citations - Craig H. Wilson (Fungal Genetics Reports, 2005)
David Perkins pointed out to me that research articles dealing with Neurospora do not always include the word Neurospora. There are instances where the fungus is named Chrysonilia sp. (usually C. sitophila), referring to the imperfect stage. Here follows a list of such citations, with a few caveats. In many cases, the journals in which these articles appeared are not available to me, so I generally have not confirmed these citations. Some may be only single-page abstracts. I have not attempted to find all citations using Monilia sitophila, a name in use before Chrysonilia.